Love and other brain experiments - Brohm, Hannah (Atria, 2026)
Neuroscientist Dr. Frances Silberstein has success on the brain. As a grad student, she was offered a job by her brilliant boyfriend, but determined to make it on her own, she turned it-and him-down. Now, stuck in postdoc purgatory with no job security and no personal life to speak of, Frances is desperate to make a breakthrough. Her best shot is a summer conference packed with her field's leading scientists. The only problem? It's organized by her ex, who has found the success that's eluded her. But backing out is not an option, because Frances desperately needs to network to save her career. Enter Dr. Lewis North: her perceptive, meticulous, and inconveniently attractive rival. When their academic sniping gets mistaken for flirtatious chemistry, Frances doesn't deny it-putting her integrity and career on the line. As soon as her prefrontal cortex is operational again, Frances realizes she needs to keep up the charade, or risk everything she's worked for. Faking data is out of the question, but fake dating? That might just be the solution she needs. But as Lewis starts to make her reward centers spark and a major setback has Frances questioning everything, she must confront what she's willing to chase-for love, for science, and for the future she thought she wanted.--Amazon